Analisis Yuridis Terhadap Pencemaran Lingkungan Oleh Pertambangan Rakyat Di Kabupaten Aceh Jaya - Mirza Sahputra (Puslatbang KHAN, 2019)
Mining sector in Indonesia is a sector that serves to get the largest foreign exchange of the country, but the existence of mines in Indonesia is now much questioned by various circles. Countries are often faced with dilemmatic conditions between optimal utilization and environmental and social losse. The people of Aceh Jaya are also tempted by high income in the mining sector, as is evidenced by the proliferation of unlicensed people's mining. As for the formulation of the problem is how the legal analysis of environmental pollution by people's mining in Aceh Jaya district?. The purpose of this research is to know and to explain the legal analysis toward environmental pollution caused by people mining in Aceh Jaya district.The type of research used is normative legal research, research that is focused to examine the application of norms or norms in positive law. The result of this research is that in the case of environmental pollution conducted by the people's mining in Gunong ujen Aceh Jaya, administrative sanctions can not be applied because the people's mining does not have the permit (illegal) issued by the local government, then the applicable law that is criminal sanction in case do not obtain permit and cause loss in the community. The government may stipulate the People's Mining Area because if the people's mining is done well, it is one of the local economic potentials that can drive the economy in the region.